2022
DOI: 10.3389/fpls.2022.849483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Litter and Root Manipulations on Soil Bacterial and Fungal Community Structure and Function in a Schrenk’s Spruce (Picea schrenkiana) Forest

Abstract: Soil microorganisms are the key driver of the geochemical cycle in forest ecosystem. Changes in litter and roots can affect soil microbial activities and nutrient cycling; however, the impact of this change on soil microbial community composition and function remain unclear. Here, we explored the effects of litter and root manipulations [control (CK), doubled litter input (DL), litter removal (NL), root exclusion (NR), and a combination of litter removal and root exclusion (NI)] on soil bacterial and fungal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 98 publications
1
7
0
Order By: Relevance
“…According to the bacterial genus level data of litter decomposition, the relatively high abundance of Pseudomonas (0.34-43.75%), Curvibacter (1.95-57.87%) and Flavobacterium (0.04-28.74%) might be the result of the nitrogen-xing abilities consistent with other studies (Zhu et al 2022). There were 92 genera common to all experimental groups, indicating a highly similar microbial composition (Fig.…”
Section: Changes In Bacterial Community Composition and Diversitysupporting
confidence: 88%
“…According to the bacterial genus level data of litter decomposition, the relatively high abundance of Pseudomonas (0.34-43.75%), Curvibacter (1.95-57.87%) and Flavobacterium (0.04-28.74%) might be the result of the nitrogen-xing abilities consistent with other studies (Zhu et al 2022). There were 92 genera common to all experimental groups, indicating a highly similar microbial composition (Fig.…”
Section: Changes In Bacterial Community Composition and Diversitysupporting
confidence: 88%
“…Dasiphora fruticosa and Salix oritrepha are deciduous shrubs ( Kudo et al, 2001 ; Myers-Smith et al, 2011 ), producing higher quality and more easily decomposed plant litter ( DeMarco et al, 2014 ). Research has shown that dominant plant can modify the diversity of soil microbial communities by impacting soil physicochemical properties through litter inputs ( Zhu et al, 2022 ). The aims of this study were to (1) analyze the bacterial community diversity, microbial antagonistic interaction, and soil properties under different shrub types (i.e., evergreen shrub and deciduous shrubs); and (2) analyze the pathway of deciduous shrubs’ effects on bacterial community diversity compared to evergreen shrub.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to degrade cellulose and lignins is widespread in fungi derived from soil [ 38 ], and is particularly well represented in Ascomycota and Basidiomycota [ 39 ]. Basidiomycota is positively correlated with soil C and N [ 40 ], and a large proportion of this phylum can actually form mycorrhizas with plant roots in soil [ 38 ]. Ascomycota is more prevalent in harsh habitats, while Basidiomycota tends to thrive in nutrient-rich environments [ 26 ], hence justifying its highest abundance in AF.…”
Section: Discussionmentioning
confidence: 99%